(untitled) (International Bulletin of Applied Science and Technology, 2026)
This article examines methodological approaches to developing the phraseological vocabulary of primary school students. It presents a system of exercises, a pedagogical experiment, and research results confirming the effectiveness of using phraseological units with the integration of artificial intelligence.